2017
DOI: 10.4314/njpar.v38i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of genotoxicity and anti-plasmodial activities of stem and leaf extracts of <i>Alstonia boonei</i> (De Wild) in malaria-infected mice

Abstract: Drug resistance in malaria infection is a serious public health challenge. Thus, scientific search for alternative treatment measures among the local medicinal plants is exigent. We therefore investigated the anti-plasmodial efficacy and genotoxicity of the methanolic leaf and stem extracts of Alstonia plant at varying concentration (200 mg/kg, 400 mg/kg and 600 mg/kg) in mice infected with chloroquine sensitive Plasmodium berghei. The phytochemical screening of the extract revealed that leaf sample contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In terms of chromosomes aberrations indcued, the extracts individually, and the recipe had weak genotoxic effects on A. cepa cells based on the induction of chromosomal aberrations in a non-dose dependent manner, and which are significantly lower compared to that of the postive control (0.05% sodium azide). Similar less genotoxic effect of stem-bark and leaves extracts of A. boonei was earlier reported in Swiss albino mice following the bone marrow micronucleus assay (Babamale et al, 2017). Likewise, leaf extract of A. indica had earlier been reported to cause various chromosomal aberrations in A. cepa cells and point mutations in the cells of Salmonella typhimurium TA 98 and TA 100 strains (Akaneme and Amaefule, 2012; Katabale et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In terms of chromosomes aberrations indcued, the extracts individually, and the recipe had weak genotoxic effects on A. cepa cells based on the induction of chromosomal aberrations in a non-dose dependent manner, and which are significantly lower compared to that of the postive control (0.05% sodium azide). Similar less genotoxic effect of stem-bark and leaves extracts of A. boonei was earlier reported in Swiss albino mice following the bone marrow micronucleus assay (Babamale et al, 2017). Likewise, leaf extract of A. indica had earlier been reported to cause various chromosomal aberrations in A. cepa cells and point mutations in the cells of Salmonella typhimurium TA 98 and TA 100 strains (Akaneme and Amaefule, 2012; Katabale et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…The use of herbal medicines to prevent and treat diseases should be done with some levels of toxicological consciousness due to the fact that some plants extracts are associated with toxicity. Plant extracts and herbal products have been reported to have mutagenic, genotoxic, carcinogenic teratogenic effects (Akinboro and Bakare, 2007;Akinboro et al, 2011aAkinboro et al, , 2011bSponchiado et al, 2016;Akinboro et al,2017;Babamale et al, 2017;Akinboro et al, 2020b). Herbal medicines prepared with more than one plant should always be subjected to genetic toxicological assays to establish that both the individual plant extract and the recipe itself (mixture of extracts) are safe for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the aqueous and ethanolic leaf and root extracts of A. boonei , as well as the standard drug, were effective in suppressing the level of parasitemia in the infected mice. In a comparative study of genotoxicity and anti-plasmodial activities of stem and leaf extracts of A. boonei in malaria-infected mice, chloroquine had the highest MST followed by A. boonei stem extract 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The blood schizontocidal activity of methanol root bark extracts of A. boonei against P. berghei infection in Swiss albino mice showed a significant anti-malaria potency which could be exploited in the formulation of standard anti-malaria drug 19 . Studies on ethanolic leaf 5 , methanol root bark 19 , aqueous leaf 23 , methanol stem and leaf 30 , and lime leaf 36 extracts of A. boonei and its effect on some haematological and biochemical parameters of albino mice infected with P. berghei have been conducted. None of the studies utilized aqueous and ethanolic leaf and root extract of A. boonei .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such means of treating diseases still play important roles in such countries (2,3). However, there is a need for scientific studies on such plants to ascertain their safety, dosage, and efficacy as alternatives to orthodox medicines and evaluate their chemical composition for potential drug discoveries (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%